2018
DOI: 10.1186/s13063-018-2751-z
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening mental health and research training in Sub-Saharan Africa (SMART Africa): Uganda study protocol

Abstract: BackgroundChildren in Sub-Saharan Africa (SSA) comprise half of the total regional population, yet existing mental health services are severely under-equipped to meet their needs. Although effective interventions for the treatment of disruptive behavioral disorders (DBDs) in youth have been tested in high-poverty and high-stress communities in developed countries, and are relevant for widespread dissemination in low- and middle-income countries (LMICs), most of these evidence-based practices (EBPs) have not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 107 publications
0
32
0
Order By: Relevance
“…The pertinence of illuminating the relationship between psychosis and other mental health problems or emotional conditions has been well articulated (Kelleher et al, 2012;Subramaniam et al, 2014). Given the small attention granted to PLEs and other mental health problems in Africa (Sankoh et al, 2018;Ssewamala et al, 2018), the present study contributed to the literature by exploring the association between PLEs and depression and anxiety symptoms, suicidal tendency and mental wellbeing. First, it was observed that negative PLEs dimensions were significantly related to the symptoms of depression, anxiety and suicidal tendency.…”
Section: Discussionmentioning
confidence: 95%
“…The pertinence of illuminating the relationship between psychosis and other mental health problems or emotional conditions has been well articulated (Kelleher et al, 2012;Subramaniam et al, 2014). Given the small attention granted to PLEs and other mental health problems in Africa (Sankoh et al, 2018;Ssewamala et al, 2018), the present study contributed to the literature by exploring the association between PLEs and depression and anxiety symptoms, suicidal tendency and mental wellbeing. First, it was observed that negative PLEs dimensions were significantly related to the symptoms of depression, anxiety and suicidal tendency.…”
Section: Discussionmentioning
confidence: 95%
“…For example, studies from Kenya focused predominantly on the cultural appropriateness and usefulness of psychosis screening measures, as well as prevalence of psychosis in non-clinical samples (Mamah et al, 2012(Mamah et al, , 2016(Mamah et al, , 2013(Mamah et al, , 2014Owoso et al, 2018Owoso et al, , 2014, as opposed to the demographic and clinical profiling of individuals diagnosed with psychosis in South Africa (Paruk et al, 2013(Paruk et al, , 2015(Paruk et al, , 2017(Paruk et al, , 2018(Paruk et al, , 2009. This review has largely corroborated early suggestion that mental health in general (Charlson et al, 2014;Cortina et al, 2012;Sipsma et al, 2013) and mental health research in particular (Sankoh et al, 2018;Ssewamala et al, 2018) has been granted scant attention in Africa for reasons such budgetary constraints (Chisholm et al, 2019) and limited human resource (Cortina et al, 2012;Roberts et al, 2014;Sankoh et al, 2018). In their review of publications from Africa in Lancet Global Health, Sankoh et al (2018) found that a search for "mental health disorders" in Africa produces just 16 items, whereas Cortina et al (2012) investigations into the prevalence of mental health problems in individuals aged up to 16 years in Sub-Saharan Africa yielded only 10 eligible studies.…”
Section: Discussionmentioning
confidence: 63%
“…59, December, 2020 SENSOY BAHAR ET AL. / 1941 may influence uptake, implementation, integration, and youth outcomes (see Ssewamala et al, 2018 for study specific details).…”
Section: Discussionmentioning
confidence: 99%